2007
DOI: 10.1097/00000542-200703000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Cerebral Ischemic Tolerance by Erythromycin Preconditioning Reprograms the Transcriptional Response to Ischemia and Suppresses Inflammation

Abstract: These findings present a new molecular correlate for the induction of ischemic tolerance achieved by erythromycin preconditioning and will further the understanding of this clinically important new regimen of preemptive neuroprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
2
3

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
1
23
2
3
Order By: Relevance
“…In contrast to the findings of Stenzel-Poore et al (2003) and Koerner et al (2007), we found a modestly higher proportion of upregulated than downregulated genes in the preconditioning-treated groups after both 3-h and 16-h reperfusions. This disparity is likely due to either the focus of our expression analyses on the apoptosis and PI3K-Akt pathway-associated genes as opposed to a global gene expression analysis or due to the use of a homogeneous in vitro culture sample.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the findings of Stenzel-Poore et al (2003) and Koerner et al (2007), we found a modestly higher proportion of upregulated than downregulated genes in the preconditioning-treated groups after both 3-h and 16-h reperfusions. This disparity is likely due to either the focus of our expression analyses on the apoptosis and PI3K-Akt pathway-associated genes as opposed to a global gene expression analysis or due to the use of a homogeneous in vitro culture sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Global gene expression studies using in vivo models of preconditioning have shown that, while ischemia alone induces an overall upregulation of gene expression, the pattern in preconditioned brains is one of widespread downregulation (Stenzel-Poore et al 2003;Koerner et al 2007). In contrast to the findings of Stenzel-Poore et al (2003) and Koerner et al (2007), we found a modestly higher proportion of upregulated than downregulated genes in the preconditioning-treated groups after both 3-h and 16-h reperfusions.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Pre-ischemic conditioning has long been recognised as a powerful 23,31 . Erythromycin is a highly promising candidate for clinical application as a tolerance-inducing drug in conditions with high risk for cerebral ischemia, such as during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite erythromycin's ability to affect cerebral ischemic tolerance, the molecular mechanisms that underlie this pharmacological tolerance induction have yet to be identified. Sustained preconditioning regimens have been associated with de novo protein synthesis via adapted gene transcription, suggesting that erythromycin may act at the transcriptional level 23,31 .…”
Section: Discussionmentioning
confidence: 99%